Diseño de un sistema de mantenimiento productivo total para el mejoramiento de la productividad en el área de tejido a punto en la empresa Tejimar. - Mayo Vargas, Cristian Alexis (2022)
The objective of this degree project is the "Design of a total productive maintenance system for the improvement of productivity in the knitting area in the company TEJIMAR'', is the number one brand of woven children's clothing, has the support of Ecuadorian raw material of first quality, as well as European textile machinery that allows them to capture beautiful and delicate fabrics. In the company there is little technical documentation of the machinery which is required for the maintenance system, and the department responsible for these activities performs corrective maintenance, i.e., intervene when there is a failure or breakdown in the machinery causing unscheduled maintenance stops and consequently affects the productivity of the company. In order to solve this problem, a Total Productive Maintenance system was developed with the purpose of improving productivity in the 2 machines. In the development of the research, the knitting area was taken into account and 2 circular knitting machines of the Mayer & Cie relanit 4 and Jumber DKX-3 brands were chosen. In order to determine maintenance activities, information contained in the manufacturing manuals of the machines was taken into account, as well as the experience of the engineer in charge of the maintenance, with this it was possible to perform maintenance tasks for a year of execution for each machine and the frequency in which they should be performed.